Influência da ansiedade nos limiares de percepção à estimulação nociceptiva: um estudo psicofísico - F. M. Oliveira (2006)
Objective: this study was designed to verify the influence of state-anxiety on the perceptive threshold of nociceptive stimulation, through the administration of electric impulses under controlled conditions and environment. Methods: 60 male healthy participants were selected to the study, on the basis of a semi-structured interview for control purposes; participants were later divided in two sub-groups, depending on their state-anxiety levels (NAE) obtained from STAI-Y - one group of high state-anxiety level (GNEAE) and another of low state-anxiety level (GNBAE). Then, correlations between NAE and Pain Perception Thresholds (LPD) were analyzed, and differences between higher and lower state-anxiety groups were estimated regarding LPD. Results: though weak, a negative correlation between NAE and LPD was found and, above all, the LPDs of GNEAE and GNBAE groups were significantly different, with the first one evidencing a lower pain perception threshold. Conclusion: as expected, raised state-anxiety was expressed in a decreased nociceptive perception threshold. Some explanatory hypothesis are advanced for the results.